Early Recognition and Treatment of Diabetic Kidney Disease - Ahmed, Sheikh Salahuddin; Rizwan, Md Abu Saleh Mohammad; Khan, Md Abdul Mahid; Laila, Tarafdar Runa; Hafez, Md Abdul (Medicine Today, 2014)
Diabetic kidney disease (DKD) is a progressive condition and is an important cause of end stage renal disease (ESRD) as well as a risk factor for cardiovascular morbidity and mortality. This paper reviews various evidence based clinical guidelines, scientific papers and research studies on early detection and treatment of DKD. Microalbuminuria describes the urinary excretion of small amounts of albumin which identifies the early stage of DKD. In addition to an earliest marker of kidney damage, microalbuminuria is an established high risk factor for cardiovascular morbidity and mortality. Patients with microalbuminuria who progress to macroalbuminuria are likely to progress to ESRD. However effective treatment in the early stage of DKD reduces the risk and slows the progression of kidney damage. There is general agreement that people with diabetes should be screened regularly to detect early markers of kidney damage. People with diabetes and microalbuminuria should be treated with a multifactorial intervention approach to retard the progression of DKD. Studies have clearly demonstrated that the use of angiotensin converting enzyme inhibitors or angiotensin 2 receptor blockers with improved glycemic control, hypertension control, lipid lowering, aspirin use, smoking cessation, exercise programs and dietary intervention reduced the development of overt nephropathy and ESRD. DOI: http://dx.doi.org/10.3329/medtoday.v26i1.21317 Medicine Today 2014 Vol.26(1): 56-62